PENGARUH SOSIALISASI, EDUKASI, DAN LITERASI KEUANGAN TERHADAP MOTIVASI MAHASISWA UNIVERSITAS TRIATMA MULYA DALAM MEMBELI SAHAM DI PASAR MODAL - Ni Gusti Ayu Putu Ikayanti; I Gusti Agung Krisna Lestari; Ni Made Ernila Junipisa (Journal Research of Accounting, 2023)
The purpose of this study is to examine the influence of socialization, education, and financial literacy on the motivation of Triatma Mulya University students to buy stocks from the capital market. Two types of his variables are used in this study: dependent and independent variables. The dependent variable in this study is motivation (Y). On the other hand, the independent variables in this study are socialization (X1), education (X2), and financial literacy (X3). The data source used in this study was primary data in the form of questionnaires distributed to accounting students at Triatma Mulya University. Ninety-two 5th and 7th semester accounting students participated in this study. A random sample of 89 students was obtained by systematic and targeted sampling. The survey method is a quantitative survey by data analysis by multiple regression analysis using the SPSS statistical program. The results of the analysis awareness, education and financial literacy have a positive on the motivation of the students of Triatma Mulya University to buy shares in the capital market